2006
DOI: 10.4049/jimmunol.176.12.7207
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Galectin-1 Induces Maturation of Dendritic Cells That Elicit Contrasting Responses in Naive and Activated T Cells

Abstract: Dendritic cells (DC) are professional APC that control the balance between T cell immunity and tolerance. Genetic engineering of DC to regulate the outcome of the immune response is an area of intense research. Galectin (gal)-1 is an endogenous lectin that binds to glycoproteins and exerts potent regulatory effects on T cells. Consequently, gal-1 participates in central deletion of thymocytes and exerts therapeutic effects on experimental models of T cell-mediated autoimmune disorders and graft-vs-host disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 63 publications
2
56
1
Order By: Relevance
“…Furthermore, dendritic cells engineered to overexpress galectin-1 synthesized increased levels of proinflammatory cytokines and showed enhanced ability to stimulate naive T cells (45). In addition, Dias-Baruffi et al (47) demonstrated that addition of galectin-1 induces cell surface exposure of phosphatidylserine, thus favoring recognition by phagocytic leukocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, dendritic cells engineered to overexpress galectin-1 synthesized increased levels of proinflammatory cytokines and showed enhanced ability to stimulate naive T cells (45). In addition, Dias-Baruffi et al (47) demonstrated that addition of galectin-1 induces cell surface exposure of phosphatidylserine, thus favoring recognition by phagocytic leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent findings indicate that galectin-3 is a critical regulator of chronic inflammation, myofibroblast activation, and hepatic fibrosis (40). Taking these findings into consideration, it has been proposed that different members of the galectin family may act in concert to regulate the initiation of the inflammatory response (41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Gals might also be stimulating different APCs to sustain T cell activation after priming. In this regard, it was reported that dendritic cells (DCs) engineered to express transgenic Gal-1 displayed an enhanced ability to stimulate naive T cells and, conversely, induced apoptosis of activated T cells (35). These Gal-1-expressing DCs exhibited a mature phenotype, as reflected by the increase in MHC and costimulatory molecule expression, as well as enhanced levels of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, gal-1 antagonized persistent TCR agonist binding in activated peripheral CD8 T cells, as determined in vitro by a tetramer decay assay and in vivo by diminished Ag-induced tetramer dulling. Together with recent findings demonstrating that gal-1 promotes agonist TCR binding and signaling during thymocyte development (8), these studies highlight how a single lectin can differentially modulate TCR binding and functional outcome, depending on the developmental and activation stage of the T cell (34). These data also demonstrate that induced gal-1 expression by activated CD8 T cells regulates T cell proliferation vs apoptosis by opposing continued agonist TCR binding and signal transduction, identifying a novel mechanism by which TCR avidity can be modulated in peripheral CD8 cells to affect functional outcome.…”
Section: Galectin-1 (Gal-1)mentioning
confidence: 99%